Official statement Covid-19 crisis amendment to new dates for physical admission to campus for semester II, academic session 2020 2021 - UMP, PNC (2021)
1. Universiti Malaysia Pahang (UMP) had issued an official statement regarding the Students Physical Admission to Campus for Semester II, 2020/2021 on 2 February 2021 and the government’s announcement on the extension of the Movement Control Order (MCO) for all states except Sarawak until 18 February 2021.